Bug-A-Boo With and Without D.D.T. Kills All 9 Major Pests - Socony-Vacuum Oil Company
Color-print advertisement for Socony-Vacuum Bug-a-boo insecticide. An illustration of three cartoon mosquitos fleeing from a pesticide sprayer fills the top portion of the page. Two Bug-a-boo bottles are illustrated on the lower right side of the page. Socony-Vacuum Company was formed in 1931 with the merger of Standard Oil and the Vacuum Oil Company. The company rebranded to become the Mobil Corporation in 1963, and exists today as ExxonMobil after merging with the Exxon corporation in 1999.
Keywords: DDT (Insecticide); Insecticides; Pests--Control; Socony-Vacuum Oil Company